2017
DOI: 10.3389/fnana.2017.00002
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Viral Vectors Serotype 8 for Cell-Specific Delivery of Therapeutic Genes in the Central Nervous System

Abstract: Adeno-associated viruses (AAVs) have become highly promising tools for research and clinical applications in the central nervous system (CNS). However, specific delivery of genes to the cell type of interest is essential for the success of gene therapy and therefore a correct selection of the promoter plays a very important role. Here, AAV8 vectors carrying enhanced green fluorescent protein (eGFP) as reporter gene under the transcriptional control of different CNS-specific promoters were used and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…In murine models, AAV8 is known for its ability to widely transduce the brain after intracranial administration 32 , 33 . After systemic injection, most of the organs and especially the liver are successfully targeted 35 but the neurotropism is influenced by the age of infusion and the dose of vector administered.…”
Section: Discussionmentioning
confidence: 99%
“…In murine models, AAV8 is known for its ability to widely transduce the brain after intracranial administration 32 , 33 . After systemic injection, most of the organs and especially the liver are successfully targeted 35 but the neurotropism is influenced by the age of infusion and the dose of vector administered.…”
Section: Discussionmentioning
confidence: 99%
“…In murine animal models, AAV8 is known for its ability to widely transduce the brain after intracranial administration 36,37 . After systemic injection, most of the organs and especially the liver are successfully targeted 38 but the neurotropism is influenced by the age of infusion and the dose of vector administered.…”
Section: Discussionmentioning
confidence: 99%
“…neuronopathic Gaucher disease, mucopolysaccharidosis type I and II). Depending on the pathophysiology of the disease, specific brain cell-types can be selectively targeted in modifying either promoter and/or age at injection 36,37 . The animal was placed in the centre of a plastic box (40 x 40 cm floor) and video-recorded for 5 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that serotype of AAV virus could affect cell-type specificity of virus infection, as many studies previously reported [ 22 23 24 ]. Natural AAV viruses have a specific pattern of infection that reflects the interaction and recognition between the viral capsid, envelope and receptors expressed in susceptible cells.…”
Section: Discussionmentioning
confidence: 99%